1980
DOI: 10.3171/jns.1980.52.4.0525
|View full text |Cite
|
Sign up to set email alerts
|

Direct percutaneous cerebral angiography in neurosurgical practice

Abstract: A retrospective analysis of 1171 consecutive percutaneous retrograde brachial and carotid cerebral angiograms was performed on 635 patients, 50.7% of whom were in the sixth decade or older. Symptoms and signs of cerebrovascular disease were the most frequently investigated and diagnosed, accounting for 46.7% of all the angiograms. Despite this relatively high-risk population, we have found direct percutaneous cerebral angiography to have a very low risk. The pros and cons of direct percutaneous versus transfem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The transcarotid approach has been described as a viable alternative for vascular access in several other procedures, such as aortic repair interventions, 2 cerebral angiography, 3 endovascular intervention for acute ischemic stroke, 4,5 complex pediatric cardiac interventions, 6,7 and transcatheter aortic valve implantation (TAVI). [8][9][10] One case of a diagnostic coronary catheterization via transcarotid approach has also been described.…”
Section: Discussionmentioning
confidence: 99%
“…The transcarotid approach has been described as a viable alternative for vascular access in several other procedures, such as aortic repair interventions, 2 cerebral angiography, 3 endovascular intervention for acute ischemic stroke, 4,5 complex pediatric cardiac interventions, 6,7 and transcatheter aortic valve implantation (TAVI). [8][9][10] One case of a diagnostic coronary catheterization via transcarotid approach has also been described.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Jadhav et al 6 reported complications (one large hematoma and one pseudoaneurysm) in both cases of closure with the Mynx device (AccessClosure, Mountain View, USA), whereas no complications were seen when manual compression was applied. While some authors advocate manual compression of the carotid puncture site,6 16 19 20 other authors point out a considerable risk for cervical hematoma, especially when double platelet inhibition or aggressive heparin treatment is needed 9 15 21. Altogether, local puncture-related complications (dissections and local hematomas) after percutaneous carotid puncture have been reported in 2.4–10.7% of cases in large series 21…”
Section: Discussionmentioning
confidence: 99%
“…Given the overall smaller risk of local complications compared with percutaneous puncture, various authors strongly recommended open exposure instead of transcutaneous puncture of the carotid artery in order to reduce the risk of vessel injuries, in particular when patients have vascular fragility such as Marfan disease or Ehlers–Danlos syndrome 9 13. In addition, postprocedural surgical closure of the access site is more effective than closure after percutaneous carotid puncture, allowing double platelet inhibition and more aggressive heparin treatment with a lower risk for hematomas 15 21 24–28…”
Section: Discussionmentioning
confidence: 99%
“…Direct carotid puncture (DCP) played a historical part in the development of cerebral angiography but has since then been relegated and is no longer used unless an alternative access is not possible. 3 We present two cases in which a distal approach was unsuccessful to perform CAS and a DCP was used successfully.…”
mentioning
confidence: 98%